Salinity-independent dissipation of antibiotics from flooded tropical soil: a microcosm study - Sentek, Valerie; Braun, Gianna; Braun, Melanie; Sebesvari, Zita; Renaud, Fabrice G.; Herbst, Michael; Frindte, Katharina; Amelung, Wulf (Scientific Reports, 2020)
River deltas are frequently facing salinity intrusion, thus challenging agricultural production in these areas. One adaption strategy to increasing salinity is shrimp production, which however, heavily relies on antibiotic usage. This study was performed to evaluate the effect of increasing salinity on the dissipation rates of antibiotics in tropical flooded soil systems. For this purpose, paddy top soil from a coastal Vietnamese delta was spiked with selected frequently used antibiotics (sulfadiazine, sulfamethazine, sulfamethoxazole, trimethoprim) and incubated with flood water of different salt concentrations (0, 10, 20 g L −1 ). Antibiotic concentrations were monitored in water and soil phases over a period of 112 days using liquid chromatography and tandem mass spectrometry. We found that sulfamethazine was the most persistent antibiotic in the flooded soil system (DT 50 = 77 days), followed by sulfadiazine (DT 50 = 53 days), trimethoprim (DT 50 = 3 days) and sulfamethoxazole (DT 50 = 1 days). With the exception of sulfamethoxazole, the apparent distribution coefficient increased significantly ( p < 0.05) for all antibiotics in course of the incubation, which indicates an accumulation of antibiotics in soil. On a whole system basis, including soil and water into the assessment, there was no overall salinity effect on the dissipation rates of antibiotics, suggesting that common e-fate models remain valid under varying salinity.